Operationalising performance measurement dimensions for the Australasian nonprofit healthcare sector. Issue 6 (10th October 2016) - Soysa, Ishani Buddika; Jayamaha, Nihal Palitha; Grigg, Nigel Peter
Abstract : Purpose: The purpose of this paper is to develop a performance measurement (PM) framework for Australasian nonprofit organisations (NPOs) involved in healthcare, and operational descriptions for each PM dimension within this framework. Design/methodology/approach: Literature relating to the balanced scorecard and other PM frameworks was examined to develop an initial conceptual model, and this model was substantially improved by collecting qualitative data from nine Australian and New Zealand healthcare NPOs using a case study approach. Findings: The study identifies nine causally related PM dimensions: mission, strategy, organisational capabilities, infrastructure and people development (people and information), financial health, processes, and stakeholder satisfaction (clients, people, and donors). The study also recognised that "Mission" and "Strategy" should be PM dimensions and that healthcare NPOs should focus on satisfying its people, not only donors and clients. Additionally, 41 operational descriptions are developed for each of these dimensions and can enable detailed PM items to be derived by organisations. Originality/value: The study is the first study that has been undertaken to develop a PM framework for the Australasian NPOs to a level that it can be readily used by the practitioners (following customisation to their own specific context). The developed model also serves as a basis for future quantitative academic research aimed at testing and empirical validation of the conceptual model.